Impact Property of PLA/Flax Nonwoven Biocomposite. (3rd October 2013) - Alimuzzaman, Shah; Gong, R. H.; Akonda, Mahmudul
Abstract : Flax fibre reinforced polylactic acid (PLA) biocomposites were fabricated by using a new technique incorporating an air-laying nonwoven web forming process and compression moulding technologies. The relationship between the main process variables and the properties of the biocomposite was investigated. The results show that with the increasing of flax content, the notched Izod impact strength increased. The maximum value of 28.3 KJ/m 2 was achieved at 60% flax fibre content. As the moulding temperature and moulding time increased, the impact strength decreased. The physical properties of the biocomposites were also evaluated. As the flax fibre content increased, the void content of the biocomposites increased. This was further confirmed by the surface morphology of the composite material. The appropriate processing parameters for the biocomposites were established.